Peer review on the studies of nutrient leaf concentration for Bertholletia excelsa Bonp. - Damaceno, João Batista Dias; Lobato, Ana Cecília Nina; Oliveira, Danielle Monteiro de (Revista Ecologia e Nutrição Florestal - ENFLO, 2019)
The adequate nutrients supply for Brazil nut (Bertholletia excelsa Bonp.) facilitates its management for economic or ecological purposes. However, the lack of sufficiency ranges for foliar concentrations of primary and secondary macronutrients makes it difficult to interpret the nutritional requirement of the crop. Thus, the objective of this study is to characterize the nutritional aspects about Bertholletia excelsa, based on the peer review of the leaf and macro levels of micronutrients in plants grown in Brazil. The study is based on eight published of Bertholletia excelsa, which were analyzed using descriptive statistics. Macro and micronutrient ranges were defined according to the mean of the minimum and maximum levels verified between the studies and the values were estimated at low, normal and high for each nutrient. There was great variation between macronutrient values. Nitrogen is accumulated in a larger quantity in the leaves of Bertholletia excelsa and, where the leaf accumulation follows the order: N> K> Ca> Mg> S> P. The nutrient foliar concentrations observed in the literature are consistent with the foliar ranges proposed by this study for plants of Brazil nut.